Pembebasan Narapidana melalui Asimilasi dan Integrasi dalam Perspektif Asas Salus Populi Suprema Lex Esto - Akmal, Fathurrahman; Arbani, Tri Suhendra (Alauddin Law Development Journal (ALDEV), 2023)
This study examines the substance of the KEMENKUMHAM Decree Number M. Hh-19.Pk.01.04.04 of 2020 in the handling of Covid-19, as well as the relevance of assimilation and integration with the principle of "Salus Populi Suprema Lex Esto". Literature research with a conceptual approach is used to analyze legislation and Related Literature. The results showed that the Prevention of the spread of the virus in prisons and detention centers is difficult to implement due to over-capacity conditions. Government efforts are needed to reduce the number of prisoners to maintain their health under the Correctional law. Restrictions on access in and out of Prisons and detention centers are important, while reducing the number of inmates is counterproductive. Prison clusters are evidence of the importance of attention to alarming prison conditions.